2017
DOI: 10.1371/journal.pone.0186660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostic accuracy of magnetic resonance elastography and Fibroscan for detecting liver fibrosis in chronic hepatitis B patients: A systematic review and meta-analysis

Abstract: AimThis systematic review and meta-analysis was carried out to compare the diagnostic accuracy of Magnetic resonance elastography (MRE) and Fibroscan for detecting liver fibrosis in Chronic Hepatitis B (CHB) patients.MethodsThe PubMed, the Cochrane Library, and the Web of science databases were searched for studies that evaluated the diagnostic value of MRE and Fibroscan for liver fibrosis in CHB patients until March 1st 2017. The quality of the included studies was assessed by the revised Quality Assessment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 39 publications
2
43
0
4
Order By: Relevance
“…It has been reported that the proposed cutoff values ranged from 5.2 to 8.7 kPa to diagnose significant fibrosis, 8.1 to 10.5 kPa to diagnose advanced fibrosis, and 9.4 to 14 kPa to diagnose cirrhosis. 6,18,19 In our study, the calculated cutoff values (9.9 kPa for significant fibrosis, 10.5 kPa for advanced fibrosis, and 11.2 kPa for cirrhosis) were between the corresponding ranges except the cutoff value for diagnosing significant fibrosis. LSM was found to be influenced by liver inflammation, 8,20 and there were 59.0% (328/ 556) patients with moderate to severe inflammation (HAI ≥ 5) in the present study.…”
Section: Discussionmentioning
confidence: 52%
“…It has been reported that the proposed cutoff values ranged from 5.2 to 8.7 kPa to diagnose significant fibrosis, 8.1 to 10.5 kPa to diagnose advanced fibrosis, and 9.4 to 14 kPa to diagnose cirrhosis. 6,18,19 In our study, the calculated cutoff values (9.9 kPa for significant fibrosis, 10.5 kPa for advanced fibrosis, and 11.2 kPa for cirrhosis) were between the corresponding ranges except the cutoff value for diagnosing significant fibrosis. LSM was found to be influenced by liver inflammation, 8,20 and there were 59.0% (328/ 556) patients with moderate to severe inflammation (HAI ≥ 5) in the present study.…”
Section: Discussionmentioning
confidence: 52%
“…+++++AUC ≥0.90, ++++AUC 0.85–0.89, +++AUC 0.80–0.84, ++AUC 0.75–0.79, +AUC <0.75 (Harrell’s c index substituted for AUC for prognostic category).ICC based on phantoms for sonographic elastography techniques128 and patients for MRE 47*Accuracy for determining advanced (bridging) fibrosis abstracted from meta-analyses where available or large patient cohorts 24 27 54 55 129†Proportion of cases falling within an indeterminate range for the prediction of advanced fibrosis 124 130…”
Section: Elastographymentioning
confidence: 99%
“…*Accuracy for determining advanced (bridging) fibrosis abstracted from meta-analyses where available or large patient cohorts 24 27 54 55 129…”
Section: Elastographymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we were not able to compare VCTE to other serum algorithms or magnetic resonance elastography. (40) Notwithstanding these limitations, our study is one of very few studies on noninvasive assessment compared with liver histology in this understudied population.…”
Section: Discussionmentioning
confidence: 93%